1984
DOI: 10.2754/avb198453030137
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Hematological Reference Values in Calves and Their Significance for Health Control

Abstract: Bouda ]., P. Jagos: Biochemical and Hematological Re/erence Values in Calves and Their Significance/or Health Control. Acta vet. Brno, 53,1984: 137-142. Clinical and biochemical examination of 114 calves from birth to the age of 6 months was carried out. Blood samples were taken from v. jugularis prior to the first colostrum intake and after 1,4,7,21,42,60,90 and 180 days. From the total number of 114 followed calves reference biochemical and hematological values were obtained from the group of 53 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 5 publications
1
14
1
2
Order By: Relevance
“…1990; R 0 u sse 1 and K a sa r i 1990). Before IV rehydration there was hyperkalemia in both groups of diarrhoeic calves as compared with the values after IV rehydration or the reference values stated by Bouda and Jagos (1984). Hyperkalemia occurs in severely diarrhoeic calves, because H ions diffuse from acid plasma into the intracellular fluid compartment and in order to maintain electroneutrality, K ions diffuse into the plasma.…”
Section: Discussionmentioning
confidence: 81%
“…1990; R 0 u sse 1 and K a sa r i 1990). Before IV rehydration there was hyperkalemia in both groups of diarrhoeic calves as compared with the values after IV rehydration or the reference values stated by Bouda and Jagos (1984). Hyperkalemia occurs in severely diarrhoeic calves, because H ions diffuse from acid plasma into the intracellular fluid compartment and in order to maintain electroneutrality, K ions diffuse into the plasma.…”
Section: Discussionmentioning
confidence: 81%
“…The age and nutrition of evaluated animals are the important factors that may affect the concentrations of frequently analyzed biochemical variables. Bouda and Jagoš (1984) reported that when diagnosing metabolic disorders in calves, there is a need to consider the developing immune system, labile homeostasis, functions and immaturity of body organs, and changes relating to the age of animals.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma mineral contents were within the normal ranges for three-month-old calves (Bouda and Jagos, 1984;Dalton, 1967;Friedrich et al, 1986;Reece and Wahlstrom, 1972) with the exception of Mg, the level of which (0.38 mmol/1) indicated subclinical hypomagnesemia (Ivins and Alcroft, 1969;Smith, 1957). The probable cause was insufficient intake with the diet (the limited amount of concentrate in the ration) additionally influenced by natural factors (low constitutional Mg reserves, low utilization of Mg in the feed) that intensify hypomagnesemia in calves (Bomba et al, 1993).…”
Section: Resultsmentioning
confidence: 81%